Preparation method of high-thermal-conductivity polymer taking modified boron nitride as filler
By aminating the boron nitride nanosheets and compounding them with carbon nanotubes, the problems of low thermal conductivity and high interface thermal resistance of polymer materials are solved, and polymer materials with high thermal conductivity are achieved, suitable for electronic equipment heat dissipation needs.
Patent Information
- Application Number
- CN202411733439.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-01-14
AI Technical Summary
The thermal conductivity of existing polymer materials is low and cannot meet the requirements of efficient heat dissipation. The poor compatibility of boron nitride nanosheets with polymer matrix leads to high interface thermal resistance, which limits the performance of their thermal conductivity.
By aminating the boron nitride nanosheets and compounding them with carbon nanotubes, a composite thermal conductivity filler is formed. The dispersion and orientation of the filler are improved through ultrasonic treatment and freezing orientation technology, a thermal conductivity network is constructed, and high thermal conductivity polymerization is prepared. Things.
The interface compatibility and dispersion between boron nitride nanosheets and polymer matrix is significantly improved, the thermal conductivity of the polymer is enhanced, and the material with high thermal conductivity is formed, which is suitable for heat dissipation applications of electronic equipment.
Smart Images

Figure FT_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer thermal conductivity, and in particular to a method for preparing a high thermal conductivity polymer using modified boron nitride as filler. Background Art
[0002] With the advent of the 5G era, electronic components are developing in the direction of integration, miniaturization and functionality. These devices will generate a lot of heat during the operation of high power density. If the heat cannot be dissipated in time, it will have a serious adverse effect on the safety, working efficiency and service life of electronic equipment. Therefore, developing efficient heat dissipation materials to solve the problem of heat accumulation during the operation of equipment has become a key step in the development of electronic equipment.
[0003] Polymer materials are widely used in electronic components and integrated circuits due to their low cost, easy processing, low density, good electrical insulation and good heat resistance. However, most polymers have low thermal conductivity and cannot meet the requirements of efficient heat dissipation. Currently, high thermal conductivity fillers are added to the polymer matrix to allow more heat to be dissipated through the pathways formed by the high thermal conductivity fillers.
[0004] Boron nitride nanosheets have the characteristics of high thermal conductivity, good electrical insulation, low expansion coefficient, good thermal stability and excellent lubrication performance. They are widely used in industries such as electrical insulation and electronic components as insulating thermal conductive fillers. The original boron nitride nanosheets have poor compatibility with polymers and are prone to aggregation in the polymer matrix, which significantly increases the interfacial thermal resistance and cannot effectively exert the high thermal conductivity of the boron nitride nanosheets. Therefore, in order to reduce the interfacial thermal resistance and enhance the compatibility and dispersibility between the thermal conductive filler and the polymer, the boron nitride nanosheets need to be surface modified. Summary of the invention
[0005] The purpose of the present invention is to provide a method for preparing a highly thermally conductive polymer using modified boron nitride as a filler, which improves the interface compatibility and dispersibility between the filler and the polymer matrix, reduces the interface thermal resistance of the composite material, constructs a good thermal conductive network, and prepares a polymer with a high thermal conductivity coefficient.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A method for preparing a high thermal conductivity polymer using modified boron nitride as filler comprises preparing modified boron nitride nanosheets, preparing composite thermal conductive filler and preparing modified high thermal conductivity polymer.
[0008] Preferably, the method for preparing modified boron nitride nanosheets is to add the boron nitride nanosheets to 10 ml of tetrahydrofuran, ultrasonically disperse for 10 min at a power of 400 W, then add a modifier, react at 40°C for 2 h, then remove the tetrahydrofuran at a speed of 100 r / min in a rotary evaporator at 65°C and a pressure of 400 mmHg, then transfer to 40 ml of deionized water, and dry in an oven at 80°C for 12 h to obtain modified boron nitride nanosheets.
[0009] Preferably, the modifier is one or more of tri-amino-terminated polyetheramines T403 and T5000 and di-amino-terminated polyetheramines D230, D400 and D2000; further, the modifier is preferably di-amino-terminated polyetheramine D400; the weight ratio of the boron nitride nanosheets to the modifier is 1 to 5:20.
[0010] Preferably, the method for preparing the composite thermally conductive filler is to disperse the carbon nanotubes in 40 ml of deionized water, stir at a speed of 500 r / min for 30 min, and then ultrasonically treat for 30 min at a power of 400 W to form a uniformly dispersed suspension, add modified boron nitride nanosheets to the suspension, stir at a speed of 500 r / min for 60 min, and then ultrasonically treat for 30 min at a power of 400 W to obtain a suspension of the composite thermally conductive filler, freeze-orientate for 2 h at -60°C, and then freeze-dry for 36 h at -80°C to obtain a porous foam-like composite thermally conductive filler.
[0011] Preferably, the weight ratio of the carbon nanotubes to the modified boron nitride nanosheets is 1:20-30.
[0012] Preferably, the method for preparing the modified high thermal conductive polymer is to add the composite thermal conductive filler and polyethylene terephthalate in a certain proportion into a mixer and mix them evenly, then add them into an internal mixer for melt blending, and finally add them into a flat plate vulcanizer for hot pressing molding, and finally obtain a high thermal conductive polymer with modified boron nitride as filler.
[0013] Preferably, by weight, the composite thermal conductive filler is 20-30 parts; and the polyethylene terephthalate is 100 parts.
[0014] Preferably, the temperature range of the internal mixer is 255-280° C., the rotation speed of the rotor of the internal mixer is 50-100 r / min, and the melting time is 5-20 min.
[0015] Preferably, the hot pressing conditions of the flat-plate vulcanizer are as follows: the hot pressing temperature is 255-280° C., the hot pressing pressure is 10-15 MPa, and the hot pressing process is preheating for 5-20 min, pressing for 5-10 min, and cooling for 5-10 min.
[0016] The beneficial technical effect of the present invention is that the present invention makes the structure and properties of the boron nitride nanosheets more stable by amino modification, and effectively enhances the interfacial compatibility and dispersibility of the boron nitride nanosheets and the polymer matrix. In addition, tubular or linear one-dimensional fillers are added to compound with two-dimensional boron nitride nanosheets. The one-dimensional filler mainly plays the role of a "bridge" in the construction of the thermal conductive network, connecting adjacent boron nitride nanosheets, which is conducive to the construction of the thermal conductive network and effectively improves the thermal conductivity of the filler-filled polymer matrix. During the freezing orientation process, the solvent in the suspension will solidify into ice crystals, and the ice crystals will be oriented to form an orientation template, which will play a role of physical restriction on the one-dimensional filler and the boron nitride nanosheets, thereby promoting their orderly arrangement and forming a highly oriented thermal conductive path. Freeze drying will cause the ice crystals to sublime, thereby removing the orientation template, but the three-dimensional ordered highly oriented thermal conductive path will not disappear, and the formed composite thermal conductive filler significantly improves its dispersibility and orientation in the polymer matrix. Therefore, the polymer prepared by adding the composite filler has high thermal conductivity and can be well applied in the heat dissipation of electronic equipment. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 Thermal conductivity diagram of polymers with different boron nitride nanosheet contents. DETAILED DESCRIPTION
[0018] The following is a further detailed description of the drawings and embodiments of the present invention. The described embodiments are merely exemplary implementations of the present invention and are only used to explain the present invention, but do not limit the scope of the present invention.
[0019] This embodiment provides a method for preparing a highly thermally conductive polymer using modified boron nitride as a filler, comprising the following steps:
[0020] The method for preparing modified boron nitride nanosheets is as follows: 1 part by mass of boron nitride nanosheets is added to 10 ml of tetrahydrofuran, ultrasonically dispersed for 10 min at a power of 400 W, then 20 parts by mass of D400 are added, reacted at 40°C for 2 h, and then the tetrahydrofuran is removed at a speed of 100 r / min in a rotary evaporator at 65°C and a pressure of 400 mmHg, then transferred to 40 ml of deionized water, and dried in an oven at 80°C for 12 h to obtain modified boron nitride nanosheets.
[0021] The method for preparing the composite thermally conductive filler is as follows: dispersing 1 mass part of carbon nanotubes in 40 ml of deionized water, stirring at a speed of 500 r / min for 30 min, and then ultrasonically treating at a power of 400 W for 30 min to form a uniformly dispersed suspension, adding the prepared modified boron nitride nanosheets to the suspension, stirring at a speed of 500 r / min for 60 min, and then ultrasonically treating at a power of 400 W for 30 min to obtain a suspension of the composite thermally conductive filler, freezing the orientation treatment at -60°C for 2 h, and then freeze-drying at -80°C for 36 h to obtain a porous foam-like composite thermally conductive filler.
[0022] The method for preparing a modified high thermal conductive polymer is as follows: adding the prepared composite thermal conductive filler and 100 parts by mass of polyethylene terephthalate into a mixer and mixing them evenly; melt blending them in an internal mixer at a temperature of 260°C and a speed of 80 r / min for 10 min; and finally hot pressing them in a flat vulcanizer. The hot pressing conditions are as follows: the hot pressing temperature is 260°C, the hot pressing pressure is 12 MPa, and the hot pressing process is preheating for 10 min, pressing for 8 min, and cooling for 8 min to prepare a modified high thermal conductive polymer.
[0023] For the convenience of comparison, the experimental results are listed in Table 1.
[0024] This embodiment provides a method for preparing a highly thermally conductive polymer using modified boron nitride as a filler, comprising the following steps:
[0025] The method for preparing modified boron nitride nanosheets is as follows: 2 parts by mass of boron nitride nanosheets are added to 10 ml of tetrahydrofuran, ultrasonically dispersed for 10 min at a power of 400 W, then 20 parts by mass of D400 are added, reacted at 40°C for 2 h, and then the tetrahydrofuran is removed at a speed of 100 r / min in a rotary evaporator at 65°C and a pressure of 400 mmHg, then transferred to 40 ml of deionized water, and dried in an oven at 80°C for 12 h to obtain modified boron nitride nanosheets.
[0026] The method for preparing the composite thermally conductive filler is as follows: dispersing 1 mass part of carbon nanotubes in 40 ml of deionized water, stirring at a speed of 500 r / min for 30 min, and then ultrasonically treating at a power of 400 W for 30 min to form a uniformly dispersed suspension, adding the prepared modified boron nitride nanosheets to the suspension, stirring at a speed of 500 r / min for 60 min, and then ultrasonically treating at a power of 400 W for 30 min to obtain a suspension of the composite thermally conductive filler, freezing the orientation treatment at -60°C for 2 h, and then freeze-drying at -80°C for 36 h to obtain a porous foam-like composite thermally conductive filler.
[0027] The method for preparing a modified high thermal conductive polymer is as follows: adding the prepared composite thermal conductive filler and 100 parts by mass of polyethylene terephthalate into a mixer and mixing them evenly; melt blending them in an internal mixer at a temperature of 260°C and a speed of 80 r / min for 10 min; and finally hot pressing them in a flat vulcanizer. The hot pressing conditions are as follows: the hot pressing temperature is 260°C, the hot pressing pressure is 12 MPa, and the hot pressing process is preheating for 10 min, pressing for 8 min, and cooling for 8 min to prepare a modified high thermal conductive polymer.
[0028] For the convenience of comparison, the experimental results are listed in Table 1.
[0029] This embodiment provides a method for preparing a highly thermally conductive polymer using modified boron nitride as a filler, comprising the following steps:
[0030] The method for preparing modified boron nitride nanosheets is as follows: 3 parts by mass of boron nitride nanosheets are added to 10 ml of tetrahydrofuran, ultrasonically dispersed for 10 min at a power of 400 W, then 20 parts by mass of D400 are added, reacted at 40°C for 2 h, and then the tetrahydrofuran is removed at a speed of 100 r / min in a rotary evaporator at 65°C and a pressure of 400 mmHg, then transferred to 40 ml of deionized water, and dried in an oven at 80°C for 12 h to obtain modified boron nitride nanosheets.
[0031] The method for preparing the composite thermally conductive filler is as follows: dispersing 1 mass part of carbon nanotubes in 40 ml of deionized water, stirring at a speed of 500 r / min for 30 min, and then ultrasonically treating at a power of 400 W for 30 min to form a uniformly dispersed suspension, adding the prepared modified boron nitride nanosheets to the suspension, stirring at a speed of 500 r / min for 60 min, and then ultrasonically treating at a power of 400 W for 30 min to obtain a suspension of the composite thermally conductive filler, freezing the orientation treatment at -60°C for 2 h, and then freeze-drying at -80°C for 36 h to obtain a porous foam-like composite thermally conductive filler.
[0032] The method for preparing a modified high thermal conductive polymer is as follows: adding the prepared composite thermal conductive filler and 100 parts by mass of polyethylene terephthalate into a mixer and mixing them evenly; melt blending them in an internal mixer at a temperature of 260°C and a speed of 80 r / min for 10 min; and finally hot pressing them in a flat vulcanizer. The hot pressing conditions are as follows: the hot pressing temperature is 260°C, the hot pressing pressure is 12 MPa, and the hot pressing process is preheating for 10 min, pressing for 8 min, and cooling for 8 min to prepare a modified high thermal conductive polymer.
[0033] For the convenience of comparison, the experimental results are listed in Table 1.
[0034] This embodiment provides a method for preparing a highly thermally conductive polymer using modified boron nitride as a filler, comprising the following steps:
[0035] The method for preparing modified boron nitride nanosheets is as follows: 4 parts by mass of boron nitride nanosheets are added to 10 ml of tetrahydrofuran, ultrasonically dispersed for 10 min at a power of 400 W, then 20 parts by mass of D400 are added, reacted at 40°C for 2 h, and then the tetrahydrofuran is removed at a speed of 100 r / min in a rotary evaporator at 65°C and a pressure of 400 mmHg, then transferred to 40 ml of deionized water, and dried in an oven at 80°C for 12 h to obtain modified boron nitride nanosheets.
[0036] The method for preparing the composite thermally conductive filler is as follows: dispersing 1 mass part of carbon nanotubes in 40 ml of deionized water, stirring at a speed of 500 r / min for 30 min, and then ultrasonically treating at a power of 400 W for 30 min to form a uniformly dispersed suspension, adding the prepared modified boron nitride nanosheets to the suspension, stirring at a speed of 500 r / min for 60 min, and then ultrasonically treating at a power of 400 W for 30 min to obtain a suspension of the composite thermally conductive filler, freezing the orientation treatment at -60°C for 2 h, and then freeze-drying at -80°C for 36 h to obtain a porous foam-like composite thermally conductive filler.
[0037] The method for preparing a modified high thermal conductive polymer is as follows: adding the prepared composite thermal conductive filler and 100 parts by mass of polyethylene terephthalate into a mixer and mixing them evenly; melt blending them in an internal mixer at a temperature of 260°C and a speed of 80 r / min for 10 min; and finally hot pressing them in a flat vulcanizer. The hot pressing conditions are as follows: the hot pressing temperature is 260°C, the hot pressing pressure is 12 MPa, and the hot pressing process is preheating for 10 min, pressing for 8 min, and cooling for 8 min to prepare a modified high thermal conductive polymer.
[0038] For the convenience of comparison, the experimental results are listed in Table 1.
[0039] This embodiment provides a method for preparing a highly thermally conductive polymer using modified boron nitride as a filler, comprising the following steps:
[0040] The method for preparing modified boron nitride nanosheets is as follows: 5 parts by mass of boron nitride nanosheets are added to 10 ml of tetrahydrofuran, ultrasonically dispersed for 10 min at a power of 400 W, then 20 parts by mass of D400 are added, reacted at 40°C for 2 h, and then the tetrahydrofuran is removed at a speed of 100 r / min in a rotary evaporator at 65°C and a pressure of 400 mmHg, then transferred to 40 ml of deionized water, and dried in an oven at 80°C for 12 h to obtain modified boron nitride nanosheets.
[0041] The method for preparing the composite thermally conductive filler is as follows: dispersing 1 mass part of carbon nanotubes in 40 ml of deionized water, stirring at a speed of 500 r / min for 30 min, and then ultrasonically treating at a power of 400 W for 30 min to form a uniformly dispersed suspension, adding the prepared modified boron nitride nanosheets to the suspension, stirring at a speed of 500 r / min for 60 min, and then ultrasonically treating at a power of 400 W for 30 min to obtain a suspension of the composite thermally conductive filler, freezing the orientation treatment at -60°C for 2 h, and then freeze-drying at -80°C for 36 h to obtain a porous foam-like composite thermally conductive filler.
[0042] The method for preparing a modified high thermal conductive polymer is as follows: adding the prepared composite thermal conductive filler and 100 parts by mass of polyethylene terephthalate into a mixer and mixing them evenly; melt blending them in an internal mixer at a temperature of 260°C and a speed of 80 r / min for 10 min; and finally hot pressing them in a flat vulcanizer. The hot pressing conditions are as follows: the hot pressing temperature is 260°C, the hot pressing pressure is 12 MPa, and the hot pressing process is preheating for 10 min, pressing for 8 min, and cooling for 8 min to prepare a modified high thermal conductive polymer.
[0043] For the convenience of comparison, the experimental results are listed in Table 1.
[0044] Comparative Example 1 provides a method for preparing a high thermal conductivity polymer using unmodified boron nitride as filler. Compared with Example 1, the difference is that the boron nitride nanosheets are not modified and carbon nanotubes are not added. Specifically,
[0045] The method for preparing a high thermal conductive polymer is as follows: 1 part by mass of unmodified boron nitride nanosheets and 100 parts by mass of polyethylene terephthalate are added into a mixer and mixed evenly; the mixture is melt-blended in an internal mixer at a temperature of 260°C and a speed of 80 r / min for 10 min; and finally, the mixture is hot-pressed in a flat vulcanizer under the following conditions: the hot-pressing temperature is 260°C, the hot-pressing pressure is 12 MPa, and the hot-pressing process is preheating for 10 min, pressing for 8 min, and cooling for 8 min to prepare a high thermal conductive polymer.
[0046] For the convenience of comparison, the experimental results are listed in Table 1.
[0047] Comparative Example 2 provides a method for preparing a highly thermally conductive polymer using modified boron nitride as filler. Compared with Example 1, the difference is that no carbon nanotubes are added, specifically:
[0048] The method for preparing modified boron nitride nanosheets is as follows: 1 part by mass of boron nitride nanosheets is added to 10 ml of tetrahydrofuran, ultrasonically dispersed for 10 min at a power of 400 W, then 20 parts by mass of D400 are added, reacted at 40°C for 2 h, and then the tetrahydrofuran is removed at a speed of 100 r / min in a rotary evaporator at 65°C and a pressure of 400 mmHg, then transferred to 40 ml of deionized water, and dried in an oven at 80°C for 12 h to obtain modified boron nitride nanosheets.
[0049] The method for preparing a modified high thermal conductive polymer is as follows: adding the prepared modified boron nitride nanosheets and 100 parts by mass of polyethylene terephthalate into a mixer and mixing them evenly; melt blending them in an internal mixer at a temperature of 260°C and a speed of 80 r / min for 10 min; and finally hot pressing them in a flat vulcanizer. The hot pressing conditions are as follows: the hot pressing temperature is 260°C, the hot pressing pressure is 12 MPa, and the hot pressing process is preheating for 10 min, pressing for 8 min, and cooling for 8 min to prepare a modified high thermal conductive polymer.
[0050] For the convenience of comparison, the experimental results are listed in Table 1.
[0051] Comparative Example 3 provides a method for preparing a high thermal conductivity polymer using unmodified boron nitride as filler. Compared with Example 1, the difference is that the boron nitride nanosheets are not modified, specifically:
[0052] The method for preparing the composite thermally conductive filler is as follows: dispersing 1 mass part of carbon nanotubes in 40 ml of deionized water, stirring at a speed of 500 r / min for 30 min, and then ultrasonically treating at a power of 400 W for 30 min to form a uniformly dispersed suspension, adding 1 mass part of unmodified boron nitride nanosheets to the suspension, stirring at a speed of 500 r / min for 60 min, and then ultrasonically treating at a power of 400 W for 30 min to obtain a suspension of the composite thermally conductive filler, freezing the orientation treatment at -60°C for 2 h, and then freeze-drying the treatment at -80°C for 36 h to obtain a porous foam-like composite thermally conductive filler.
[0053] The method for preparing the modified high thermal conductive polymer is as follows: adding the prepared composite thermal conductive filler and 100 parts by mass of polyethylene terephthalate into a mixer and mixing them evenly; melt blending them in an internal mixer at a temperature of 260°C and a speed of 80 r / min for 10 min; and finally hot pressing them in a flat vulcanizer. The hot pressing conditions are as follows: the hot pressing temperature is 260°C, the hot pressing pressure is 12 MPa, and the hot pressing process is preheating for 10 min, pressing for 8 min, and cooling for 8 min to prepare the high thermal conductive polymer.
[0054] For the convenience of comparison, the experimental results are listed in Table 1.
[0055] Thermal conductivity test: According to GB / T 42919.1-2023 method, the thermal conductivity of the thermal conductive polymer was tested using a thermal conductivity analyzer. The size of the thermal conductive polymer was 20 mm × 20 mm × 3 mm. The test results are shown in Table 1.
[0056] Tensile strength test: According to GB / T 1040-1992 “Plastic Tensile Test Method”, the thermal conductive polymers of each embodiment and comparative example were made into Type I specimens and subjected to tensile strength tests at a rate of 10 mm / min. The test results are shown in Table 1.
[0057] Table 1.
[0058] Boron Nitride Nanosheets D400 Carbon Nanotubes Polyethylene terephthalate Thermal conductivity (W / (m·k)) Tensile strength (MPa) Example 1 1 20 1 100 1.21 28.0 Example 2 2 20 1 100 1.15 28.5 Example 3 3 20 1 100 1.09 29.4 Example 4 4 20 1 100 1.01 29.8 Example 5 5 20 1 100 0.92 30.2 Comparative Example 1 1 / / 100 0.46 24.1 Comparative Example 2 1 20 / 100 0.56 24.9 Comparative Example 3 1 / 1 100 0.78 25.8
[0059] As shown in Table 1, compared with Comparative Example 1, the thermal conductivity and tensile strength of Comparative Example 2 and Comparative Example 3 are improved. The thermal conductivity of Comparative Example 2 is increased from 0.46 W / (m·k) to 0.56 W / (m·k), and the thermal conductivity of Comparative Example 3 is increased from 0.46 W / (m·k) to 0.78 W / (m·k), indicating that boron nitride modification and compounding with carbon nanotube fillers can improve the thermal conductivity of the polymer.
[0060] Compared with comparative examples 1-3, the thermal conductivity and tensile strength of examples 1-5 are significantly improved. Figure 1 It can be seen that when the ratio of boron nitride nanosheets: D400 = 1:20, that is, the thermal conductivity of Example 1 is the highest, which is 1.21 W / (m·k).
[0061] This specific implementation method is only an explanation of the present application and an illustration of the preparation method, and is not a limitation of the present application. New schemes formed by deformation and improvement based on the technical features of this scheme still fall within the scope of protection of this patent.
Claims
1. A method for preparing a highly thermally conductive polymer using modified boron nitride as filler, characterized in that: It includes the preparation of modified boron nitride nanosheets, the preparation of composite thermal conductive fillers, and the preparation of modified high thermal conductive polymers.
2. The method for preparing a highly thermally conductive polymer using modified boron nitride as filler according to claim 1, characterized in that: The method for preparing the modified boron nitride nanosheets is as follows: the boron nitride nanosheets are added to 10 ml of tetrahydrofuran, ultrasonically dispersed for 10 min at a power of 400 W, then a modifier is added, reacted at 40° C. for 2 h, and then the tetrahydrofuran is removed at a speed of 100 r / min in a rotary evaporator at 65° C. and a pressure of 400 mmHg, and then transferred to 40 ml of deionized water, and dried in an oven at 80° C. for 12 h to obtain the modified boron nitride nanosheets.
3. The method for preparing modified boron nitride nanosheets according to claim 2, characterized in that: The modifier is one or more of tri-amino-terminated polyetheramines T403 and T5000 and di-amino-terminated polyetheramines D230, D400 and D2000; the weight ratio of the boron nitride nanosheets to the modifier is 1-5:
20.
4. The method for preparing a highly thermally conductive polymer using modified boron nitride as filler according to claim 1, characterized in that: The method for preparing the composite thermally conductive filler is as follows: dispersing carbon nanotubes in 40 ml of deionized water, stirring at a speed of 500 r / min for 30 min, and then ultrasonically treating at a power of 400 W for 30 min to form a uniformly dispersed suspension, adding the modified boron nitride nanosheets prepared in claim 2 to the suspension, stirring at a speed of 500 r / min for 60 min, and then ultrasonically treating at a power of 400 W for 30 min to obtain a suspension of the composite thermally conductive filler, freezing and orienting the suspension at -60°C for 2 h, and then freeze-drying the suspension at -80°C for 36 h to obtain a porous foam-like composite thermally conductive filler.
5. The method for preparing a composite thermally conductive filler according to claim 4, characterized in that: The weight ratio of the carbon nanotubes to the modified boron nitride nanosheets is 1:20-30.
6. The method for preparing a highly thermally conductive polymer using modified boron nitride as filler according to claim 1, characterized in that: The method for preparing the modified high thermal conductive polymer is: adding the composite thermal conductive filler prepared in claim 4 and polyethylene terephthalate in a certain proportion into a mixer and mixing them evenly, then adding them into an internal mixer for melt blending, and finally adding them into a flat plate vulcanizer for hot pressing molding, and finally preparing a high thermal conductive polymer with modified boron nitride as filler.
7. The method for preparing a modified highly thermally conductive polymer according to claim 6, characterized in that: By weight, the composite thermal conductive filler: 20-30 parts; polyethylene terephthalate: 100 parts.
8. The method for preparing a modified high thermal conductive polymer according to claim 6, characterized in that: The temperature range of the internal mixer is 255-280° C., the rotation speed of the internal mixer rotor is 50-100 r / min, and the melting time is 5-20 min.
9. The method for preparing a modified highly thermally conductive polymer according to claim 6, characterized in that: The hot pressing conditions of the flat plate vulcanizer are as follows: the hot pressing temperature is 255-280° C., the hot pressing pressure is 10-15 MPa, and the hot pressing process is preheating for 5-20 min, pressing for 5-10 min, and cooling for 5-10 min.
Citation Information
Patent Citations
Boron nitride composite high-thermal-conductivity insulating polymer composite material and preparation method thereof
CN110951254A
Preparation method of boron nitride nanosheet-carbon nanotube heat-conducting filler and heat-conducting composite material
CN112175238A
Polymer-based heat conduction material and preparation method thereof
CN118027609A
High-temperature-cooking-resistant high-toughness PET (polyethylene terephthalate) composite material as well as preparation method and application thereof
CN118994862A
Cited By
Preparation method of modified BN two-dimensional catalytic material and application of modified BN two-dimensional catalytic material in methane conversion
CN120325313A
Preparation method of modified BN two-dimensional catalytic material and its application in methane conversion
CN120325313B
High-entropy oxide-boron nitride composite radiation refrigeration pigment and preparation method thereof
CN120922916A
High-entropy oxide-boron nitride composite radiation refrigeration pigment and preparation method thereof
CN120922916B